Uso de dados secundários de rastreamento da frota na etapa de caracterização da problemática do sistema de transporte público - Rabay, Phelipe de Figueredo Beda (2017)
Automatic data collection systems produce a large amount of information about the public transport system. The storage of this data enables analysis that contributes to an understanding of the system, generating valuable information for its management. Among these tools, is Automatic Vehicle Location (AVL) System, that produces data of quality and with great potential to aid in the understanding of the system. Often, however, it is observed that transport agencies do not exploit the full potential of the data, they only use it to control the fleet in the operational phase. Noting the importance of understanding the problems involved in a public transport system and the difficulty of obtaining data for this purpose, this work proposes the utilization of the available fleet location data in the city of Fortaleza to verify its capacity to contribute to a characterization of the system, a fundamental step in the planning process. Thus, the main objective of this work is to propose a data adequacy methodology to verify its capacity to provide information relevant to an understanding of the public transport system. The stage of data suitability solves problems that can be the same in many cities, such as the identification of the vehicles, routes and travel direction of each stored data. The methodology uses the crossing of geographical data and electronic fare to overcome the quality problem of the available data on the fleet location. It was possible, starting from an apparently incomplete database with inconsistent information, to determine the travel times, the speed of each bus and an average of the vehicles of a certain line in any part of the itinerary, the waiting time between vehicles and a bunching formation. The results allowed important analyzis about the performance and quality of the system, extremely valuable in the planning characterization stage.